1990
DOI: 10.1111/j.1469-8137.1990.tb00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Fructan and cryoprotection in ryegrass (Lolium perenne L.)

Abstract: SUMMARYChanges in carbohydrate content and composition of ryegrass {Lolium perenne L.) cv. Reveille field-grown in Normandy were investigated from May 1987 to May 1988. During the winter period, the concentrations of high DP (degree of polymerization) fructan were the lowest whilst those of ethanol-soluble carbohydrates were the highest. Ethanol-soluble carbohydrates also accounted for most of the non-structural carbohydrates of four cultivars oi Lolium perenne field-grown in central France in January 1989. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, it has been pointed out that the role of fructans in cold acclimation remains an open question since its accumulation seems to be a result of sucrose accumulation rather than the low temperature per se (Tognetti et al 1990). Another major aspect of concern is that the accumulation of low DP fructans in cold‐acclimated plants is not sufficient to result in a significant depression of freezing point and therefore cannot be considered as efficient cryoprotectants (Gonzales et al 1990). However, it has to be considered that cryoprotection is more complex and other non‐colligative properties; for example, direct interactions of cryoprotectants with membranes or proteins contribute to survival at low temperatures (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been pointed out that the role of fructans in cold acclimation remains an open question since its accumulation seems to be a result of sucrose accumulation rather than the low temperature per se (Tognetti et al 1990). Another major aspect of concern is that the accumulation of low DP fructans in cold‐acclimated plants is not sufficient to result in a significant depression of freezing point and therefore cannot be considered as efficient cryoprotectants (Gonzales et al 1990). However, it has to be considered that cryoprotection is more complex and other non‐colligative properties; for example, direct interactions of cryoprotectants with membranes or proteins contribute to survival at low temperatures (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, it seems that the partitioning of sugars in perennial ryegrass is affected by rainfall and drought (Thomas and James, 1999), which could be part of the environmental interaction, as well as other factors such as latitude and day length. Seasonal changes also affect the composition of sugars in ryegrass (Gonzalez et al, 1990). Although the Miller et al (2001b) trial observed an increase in grass DM digestibility with high-WSC grass, other trials did not.…”
Section: High-wsc Grassmentioning
confidence: 95%
“…Freezing temperatures during spring growth may rupture plant cell walls and damage meristematic tissue (Pearce and McDonald 1978). Fructans that provide chill tolerance decrease dramatically in spring when plants are developing stem structure (Gonzalez et al 1990). Therefore, grass plants in a rapid growth phase would be more susceptible to freezing temperatures (Humphreys and Eagles 1988).…”
Section: Climatic Driversmentioning
confidence: 99%